Changes in Otx2 and Parvalbumin Immunoreactivity in the Superior Colliculus in the Platelet-Derived Growth Factor Receptor- [beta] Knockout Mice. - Zhao, Juanjuan; Urakawa, Susumu; Matsumoto, Jumpei; Li, Ruixi; Ishii, Yoko; Sasahara, Masakiyo; Peng, Yuwen; Ono, Taketoshi; Nishijo, Hisao (BioMed Research International, 2013)
The superior colliculus (SC), a relay nucleus in the subcortical visual pathways, is implicated in socioemotional behaviors. Homeoprotein Otx2 and ß subunit of receptors of platelet-derived growth factor (PDGFR- ß ) have been suggested to play an important role in development of the visual system and development and maturation of GABAergic neurons. Although PDGFR- ß -knockout (KO) mice displayed socio-emotional deficits associated with parvalbumin (PV-)immunoreactive (IR) neurons, their anatomical bases in the SC were unknown. In the present study, Otx2 and PV-immunolabeling in the adult mouse SC were investigated in the PDGFR- ß KO mice. Although there were no differences in distribution patterns of Otx2 and PV-IR cells between the wild type and PDGFR- ß KO mice, the mean numbers of both of the Otx2- and PV-IR cells were significantly reduced in the PDGFR- ß KO mice. Furthermore, average diameters of Otx2- and PV-IR cells were significantly reduced in the PDGFR- ß KO mice. These findings suggest that PDGFR- ß plays a critical role in the functional development of the SC through its effects on Otx2- and PV-IR cells, provided specific roles of Otx2 protein and PV-IR cells in the development of SC neurons and visual information processing, respectively.